Frozen sperm viability and seminiferous epithelium cytology of the coati (Nasua nasua) - Souza, F.F. [UNESP]; Martins, J.L.A. [UNESP]; Afolabi, O.O. [UNESP]; Paranzini, C.S. [UNESP]; Leme, D.P.; Silva, M.S.O.M. [UNESP]; Daros, V.F. [UNESP]; Chirinéia, V.H. [UNESP]; Lopes, M.D. [UNESP] (Elsevier, 2025)
This study aimed to describe the cells of the seminiferous epithelium collected by fine needle aspiration cytology (FNAC), reproductive tract observations, semen collection, and sperm cryopreservation from coatis (Nasua nasua). Seven adult coatis were anesthetized, the reproductive tract was examined, and semen was collected by electroejaculation and cryopreserved using an extender based on protocol for domestic dogs, except that prior to cryopreservation, no centrifugation to remove the seminal plasma was performed. Testicular FNAC was also performed on each testis. The germ cells of seminiferous epithelium were identified and had cell characteristics similar to other species except for the secondary spermatocyte which was not present. Semen samples were collected from four animals, three of which were suitable for cryopreservation, although their seminal characteristics slightly declined after freezing. Examination of the coati reproductive tract revealed well developed penile bone and preputial glands like other carnivores. The testicular length x width x height meant 2.13 × 1.7 × 1.7 cm and testicular volume meant 4.5 cm3. The sperm morphology of coati exhibited an angular head shape, which was evident in the membrane integrity fluorescence assessment. The sperm motility was between 20 and 70 %, and the concentration was between 14 and 129 × 106 sperm/mL with motility of 30.0 ± 17.32 % vs 23.33 ± 11.55 % between samples thawed at 46 °C/15s and 37 °C/30s. In conclusion, testicular FNAC can be a useful tool for evaluating testicular function based on sperm production. Our findings demonstrate that semen collection and cryopreservation in coatis can be achieved using electroejaculation, extenders, and cryopreservation protocols similar to those used for domestic dogs. While these results provide a template for semen cryopreservation in other Procyonidae species, further investigation is needed to determine the necessity of removing seminal plasma.